Interactions between subunits a and b in the rotary ATP synthase as determined by cross-linking - DeLeon-Rangel, J; Ishmukhametov, RR; Jiang, W; Fillingame, RH; Vik, SB (Elsevier, 2013)
The interaction of the membrane traversing stator subunits a and b of the rotary ATP synthase was probed by substitution of a single Cys into each subunit with subsequent Cu2+ catalyzed cross-linking. Extensive interaction between the transmembrane (TM) region of one b subunit and TM2 of subunit a was indicated by cross-linking with 6 Cys pairs introduced into these regions. Additional disulfide cross-linking was observed between the N-terminus of subunit b and the periplasmic loop connecting TM4 and TM5 of subunit a. Finally, benzophenone-4-maleimide derivatized Cys in the 2–3 periplasmic loop of subunit a were shown to cross-link with the periplasmic N-terminal region of subunit b. These experiments help to define the juxtaposition of subunits b and a in the ATP synthase.